Дозвільна процедура щодо здійснення аутстафінгу в Україні - Кравець, Василь Романович; Кравец, Василий Романович; Kravec, Vasilij (My University, 2013)
The article investigates the permitting procedures for implementation of activities of provision of personnel in Ukraine. There were considered normative acts which regulate this issue. It was concluded the need of their improvement.
Кравець В. Р. Дозвільна процедура щодо здійснення аутстафінгу в Україні / В. Р. Кравець // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 385-391.
Keywords: запозичена праця; послуга з надання персоналу; дозвіл; аутстафінг; заемный труд; услуга по предоставлению персонала; разрешение; аутстафинг; contingent labor; outstaffing services; resolution; outstaffing